2022
DOI: 10.1007/s00122-022-04197-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural variants in the barley gene pool: precision and sensitivity to detect them using short-read sequencing and their association with gene expression and phenotypic variation

Abstract: Key message Structural variants (SV) of 23 barley inbreds, detected by the best combination of SV callers based on short-read sequencing, were associated with genome-wide and gene-specific gene expression and, thus, were evaluated to predict agronomic traits. Abstract In human genetics, several studies have shown that phenotypic variation is more likely to be caused by structural variants (SV) than by single nucleotide variants. However, accurate while cos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…All five sub-populations had HOR1842 or IG128104 as parental inbreds ( Supplementary Table S1 ). From the whole genome sequencing data of the parental inbreds ( Weisweiler et al , 2022 ), followed by Sanger sequencing, we identified a not previously reported polymorphism, SNP 1945, that is unique to HOR1842 and IG128104 ( Fig. 7 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All five sub-populations had HOR1842 or IG128104 as parental inbreds ( Supplementary Table S1 ). From the whole genome sequencing data of the parental inbreds ( Weisweiler et al , 2022 ), followed by Sanger sequencing, we identified a not previously reported polymorphism, SNP 1945, that is unique to HOR1842 and IG128104 ( Fig. 7 ).…”
Section: Discussionmentioning
confidence: 98%
“…For the QTLs that fulfilled these criteria, all the genes within the confidence interval were extracted using the Morex v3 reference sequence ( Mascher et al , 2021 ). Next, variant calling data of SNPs, causing tolerated and deleterious mutations, insertion and deletions (INDELs), and predicted structural variants, obtained as described by Weisweiler et al . (2022) , were used to identify genes that were polymorphic between the two parental inbreds of the sub-population in which the QTL was detected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domesticated crops such as soybean, rice, tomato, barley, or wheat were among the first plants to attract interest in SVs (cited in Hämälä et al, 2021). Recently, cocoa ( Theobroma cacao ) and barley ( Hordeum vulgare ) were evaluated for direct effects of SVs on plant fitness and crop yield (Hämälä et al, 2021; Weisweiler et al, 2022). Both studies, although using different technologies to detect SVs - haplotype-resolved genome assembly vs. short-read sequencing - showed that SVs affect transcript abundance, and some SVs even have positive effects on fitness (including pathogen resistance).…”
Section: Future Directions For Integrating Knowledge For Breeding App...mentioning
confidence: 99%
“…While most SVs in wild accessions, as shown for cocoa, are subject to purifying selection – that is, these SVs have been selected against and are rare in the population -, several SVs in domesticated crops are associated with important traits for plant improvement, such as abiotic stress tolerance (Hämälä et al, 2021). The use of SV clusters (especially insertions) determined from short-read sequencing data in phenotypic prediction models yielded, on average, higher predictive ability than SNPs for a range of yield and plant architecture related quantitative traits in barley (Weisweiler et al, 2022). This is because (1) gene-associated SV clusters (i.e., SVs clustering within 50 bp and found within and 5 kb upstream/downstream around genes) are more likely to underlie causal genes than SNPs, a significant proportion of SVs (c.10%) is directly associated with gene-specific gene expression, and also because (3) SV clusters have less linkage disequilibrium between them, thus, collectively, making SV clusters more informative than SNPs for phenotypic prediction and genomic selection.…”
Section: Future Directions For Integrating Knowledge For Breeding App...mentioning
confidence: 99%